Police Powers and Commitments in Controlling Violence arising from Assemblies: A Comparative Study of Iranian Law and International Human Rights Law - Mehrdad Ganjali Darani; Sattar Azizi; Shahram Zarneshan (پژوهشهای حقوقی)
Freedom of association is one of the most important human rights of human beings, which also plays a serious role in the demand and realization of other human rights. In many cases, these rallies are held to protest participants against the government's policies. The peaceful holding of rallies and the important role played by the police and other security forces in securing them are among the important issues that need to be addressed. In some cases, some participants in peaceful rallies may resort to violence and the police may be forced to use force to maintain order and security. The fundamental question of this article is what are the powers and obligations of governments, especially in the use of force to control peaceful assembly? The research method of this research is analytical-descriptive and the method of collecting information is library. The results of this study show that Iran's domestic regulations are generally in line with human rights standards, but in some cases, there is a conflict between these regulations. In Law on the Use of Weapons by Armed Forces Officers, the police appear to use weapons to control illegal assemblies if other means are not effective, but in the human rights system, police can use force only in cases of legitimate self-defense.